Environmental Sustainability: The Case of a Multi-Business Packaging Organisation in South Africa - Manduth Ramchander; Manikam Michael Nadar (Journal of BRICS Studies)
South Africa contributes to greenhouse gas emissions and is vulnerable to climate change's effects on health, livelihoods, water, and food. The South African Department of Environment, Forestry and Fisheries (DEFF) supports an equitable transition to a low-carbon economy and a climate‐resilient society protected for the benefit of present and future generations. The increased awareness and requirement to protect the environment has resulted in a growing demand from environmentally conscious customers for suppliers to practice the triple bottom line that requires a balanced approach to managing people, planet, and profit. Organisations therefore must have clear environmental objectives that must be aligned with the strategic goals of the organisation, to ensure better, utilisation of the organisation’s resources, management of cost, and management of the organisation’s environmental culture.